1989
DOI: 10.3109/00207458909002148
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Lateral Eye Movements: A Second Look

Abstract: It has been suggested that conjugate lateral eye movements (CLEM) are related to cerebral lateralization. Two types of research have developed: studies examining individual differences (hemisphericity) and studies examining the type of questions used to elicit eye movements (hemispheric specialization). In a 1978 review, Ehrlichman and Weinberger questioned the notion that CLEM is related to cerebral lateralization, particularly with regard to individual differences. However, since their review, a substantial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…How ever, evidence for the validity of degree of handedness and all other applied measures can be found in the literature, for instance, significant relationships to other psychological, physiological, or anatom ical characteristics, or changes after brain lesions (e.g. Annett, 1992;Bow ers & Heilman, 1980;Charlton et al, 1989;Cow ell et al, 1993;Efron & Crandall, 1983;Efron, Dennis, & Yund, 1977;Laeng et al, 1996;Miller, 1982;Porac & Coren, 1976;Rippon , 1991;Schachter, 1994;Tan, 1990;Tenke et al, 1993;W itelson & Goldsm ith, 1991).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…How ever, evidence for the validity of degree of handedness and all other applied measures can be found in the literature, for instance, significant relationships to other psychological, physiological, or anatom ical characteristics, or changes after brain lesions (e.g. Annett, 1992;Bow ers & Heilman, 1980;Charlton et al, 1989;Cow ell et al, 1993;Efron & Crandall, 1983;Efron, Dennis, & Yund, 1977;Laeng et al, 1996;Miller, 1982;Porac & Coren, 1976;Rippon , 1991;Schachter, 1994;Tan, 1990;Tenke et al, 1993;W itelson & Goldsm ith, 1991).…”
Section: Discussionmentioning
confidence: 97%
“…If subjects have to be groupe d on the basis of their ocular dom inance, therefore, these results suggest a division into three groups rather than two. In an extensive review of lateral eye movements, Charlton et al (1989) noted that the evidence suggests a greater percentage of left-movers than rightmovers in the popula tion. This observation can be confirm ed by the present results and may be in accordance with findings from cerebral blood flow studies which have demonstrated greater right hem isphere flow in norm al participants (Charlton et al, 1989;Gur & Reivich, 1980).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Weinberger (1988) has already described the importance of disorders of frontocortical areas in schizophrenics. Moreover, the frontocortical areas are considered to be paramount for CLEM-generation (Charlton et al, 1989). Tonic hemispheric priming effects could have confounded the results: insiructions were given that the purpose of the experiment was to test verbal expressivity.…”
Section: Discussionmentioning
confidence: 99%
“…Ehrlichman and Weinberger's review (1978) has cast some doubt on the proposed relationship between the interaction of CLEMs, hemispheric activity, and content of question. However, a more recent review of the experimental literature by Charlton et al (1989) provided supportive evidence for the CLEM-model on the basis of neurophysiological studies, whose findings indicated positive relationships with other measures of laterality and correlations with stimulus content. EEG validation studies supported the CLEM-model only in part (Bakan and Svorad, 1969;Morgan et al, 1971;Warren and Haueter, 1981;Neubauer el al, 1988) because this can be due to different EEG designs.…”
Section: Introductionmentioning
confidence: 93%